1995
DOI: 10.1203/00006450-199511000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Cardiovascular and Metabolic Responses to a Single Intramuscular Dose of Betamethasone in Fetal Sheep Born Prematurely by Cesarean Section

Abstract: Although the benefits of antenatal hormone treatment are well accepted, most studies have reported only pulmonary effects. There is evidence of beneficial cardiovascular and metabolic effects in studies using chronically catheterized animals; however because of the route of administration, the results are not directly applicable to clinical strategies. We previously demons trated sign ificant pulmonary effects in animals treated antenatally with a single, direct fetal, intramuscular injection of glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 28 publications
4
32
1
Order By: Relevance
“…The protection against intraventricular hemorrhage (15,38) and necrotizing enterocolitis (3) afforded by antenatal steroid administration may result from accelerated cellular development in the brain and intestine. On the other hand, it is tempting to invoke the improved blood pressure (15,24) and cardiac output (28) observed after antenatal steroid administration as the mechanism of protection because both intraventricular hemorrhage and necrotizing enterocolitis may be associated with disturbances in organ perfusion. We hypothesized that postnatal changes in Doppler BFV and cardiac function would differ between infants whose mothers did and did not receive antenatal glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protection against intraventricular hemorrhage (15,38) and necrotizing enterocolitis (3) afforded by antenatal steroid administration may result from accelerated cellular development in the brain and intestine. On the other hand, it is tempting to invoke the improved blood pressure (15,24) and cardiac output (28) observed after antenatal steroid administration as the mechanism of protection because both intraventricular hemorrhage and necrotizing enterocolitis may be associated with disturbances in organ perfusion. We hypothesized that postnatal changes in Doppler BFV and cardiac function would differ between infants whose mothers did and did not receive antenatal glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Infants whose mothers received antenatal steroids have higher blood pressures (15) and less need for blood pressure support (15,24) than do those whose mothers did not receive steroids. In preterm lambs, antenatal glucocorticoid treatment increases both blood pressure and cardiac output (28). The effect of antenatal steroid therapy on cardiac output and regional hemodynamics in newborn premature infants has not been examined previously.…”
mentioning
confidence: 99%
“…Although we found no differences in hemodynamic measures among infants who received single versus multiple doses of antenatal steroid [current study (data not shown) and (40)], it remains possible that the glucocorticoid lessens hemodynamic disturbances in the newborn by reducing the production of inflammatory mediators. Additional studies performed on infants born to mothers with acutely symptomatic chorioamnionitis, who did not benefit from the positive effects of antenatal steroid administration on cardiac function (41,42), might better distinguish the hemodynamic effects of chorioamnionitis.…”
Section: Discussionmentioning
confidence: 99%
“…A single course of corticosteroids administered to women at risk of delivering prematurely decreases the incidence of respiratory distress syndrome, and of morbidity and mortality in neonates (Doyle et al 1986, Crowley 1995, National Institutes of Health Consensus Development Panel 1995. In animal studies, antenatal corticosteroids have been shown to exert extra-pulmonary effects (Padbury et al 1995, Berry et al 1997) including a negative impact on fetal growth (Ikegami et al 1997, Jobe et al 1998. Recent evidence in animal studies suggests that when antenatal corticosteroids disrupt the fetal hormonal/metabolic milieu, there can be far-reaching implications into the postnatal period (Nyirenda et al 1998, Gatford et al 2000, Moss et al 2001, Dodic et al 2002.…”
Section: Introductionmentioning
confidence: 99%